Photocatalytic material as well as preparation method and application thereof
By solidly loading TiO2 nanoparticles with oxygen-containing vacant positions onto activated carbon fibers treated by silane reagent, a photocatalytic material with stable catalytic interface was prepared, which solved the problem of reduced efficiency and poor stability of photocatalytic material in high humidity environments, and achieved Efficient VOCs gas treatment and long-term use stability.
Patent Information
- Application Number
- CN202310790197.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
When existing photocatalytic materials are used in high humidity environments, their catalytic efficiency is reduced and their long-term use stability is poor, making it impossible to effectively treat high-humidity VOCs gas.
By solidly loading TiO2 nanoparticles with oxygen-containing vacancies onto activated carbon fibers treated with silane reagent, a photocatalytic material with a stable catalytic interface was prepared, and the material was subjected to a high humidity environment by using C-Ti bonding and Ti+4 reduction. Maintain good catalytic effect and long-term stability.
The efficient catalytic effect and long-term use stability of photocatalytic materials in high-humidity VOCs gas treatment are achieved, which avoids the problem of water gas occupying adsorption sites, and improves the response wavelength range and interface charge transfer capability of the catalyst.
Smart Images

Figure FT_1 
Figure BDA0004313376150000111 
Figure BDA0004313376150000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste gas treatment, and specifically relates to a photocatalytic material and a preparation method and application thereof. Background Art
[0002] Volatile organic compounds (VOCs) are one of the main pollutants in the atmosphere, with the characteristics of wide sources, easy volatility and easy diffusion. At present, there are two major types of treatment and control technologies for VOCs-containing gases: destruction and recovery. Destruction methods include catalytic oxidation, biodegradation and photocatalysis, while recovery methods include adsorption, absorption, condensation and membrane treatment technology. Although these methods have their own advantages, most of them have high energy consumption, harsh operating conditions, or produce a large amount of waste, which requires further treatment. Photocatalytic oxidation, as a mild and clean advanced oxidation technology, can use solar energy to degrade VOCs into CO2. It has the advantages of high treatment efficiency and low operating costs, and is suitable for the removal of most VOCs. However, in the treatment process of high-humidity VOCs gas, the catalytic efficiency of the target pollutant is often reduced because water vapor occupies most of the adsorption sites, especially when the relative humidity is higher than 50%, the long-term operation attenuation is more serious. Therefore, for the treatment of high-humidity VOCs gas, suitable photocatalytic materials are the key to solving this technical problem.
[0003] CN110180520A discloses a method for preparing a recyclable mesoporous carbon @ TiO2 / carbon fiber (CFs) photocatalytic material, comprising the following steps: (1) dissolving ethylene glycol in acetone to obtain solution A; (2) adding mesoporous carbon spheres to solution A, and ultrasonically dispersing them to obtain suspension B; (3) adding tetrabutyl titanate to suspension B, and ultrasonically dispersing them to obtain suspension C; (4) transferring suspension C to a high-pressure reactor, and immersing carbon fibers in suspension C, and the reactants undergo a solvothermal reaction under magnetic stirring to generate a solvothermal product D; (5) ultrasonically washing and drying the solvothermal product D to obtain a mesoporous carbon @ TiO2 / carbon fiber photocatalytic material. This invention prepares photocatalytic materials through solvothermal reactions, solving the problem of separation and recovery of powdered photocatalysts during actual use. However, the photocatalytic materials prepared by this method do not consider the impact of high humidity environments on the application effect. Since water vapor will occupy most of the adsorption sites on the catalyst surface, the effect will decay after long-term use.
[0004] The literature "Preparation of TiO2 Visible Light Photocatalyst by Vacuum Activation Method and Study on Its Long-term Effect" (Wu Sanding et al., Journal of Zhejiang Sci-Tech University, Vol. 35, No. 6, November 2016) used commercial TiO2 (Degussa P25) as raw material and adopted a simple one-step vacuum activation method to prepare Ti 3+Self-doped TiO2 visible light catalyst. Methyl orange was used to simulate the target pollutant, and its catalytic performance and long-term effectiveness were studied under visible light. The results showed that under visible light irradiation, the efficiency of vacuum activated P25 in degrading methyl orange was significantly better than that of pure P25. The cycle test results showed that due to the Ti 3+ It is relatively active and easily oxidized. This catalyst is used to degrade the pollutant methyl orange, and needs to be repeatedly regenerated by vacuum activation, which consumes relatively high energy.
[0005] The document "High-efficiency photocatalytic oxidation of formaldehyde by oxygen-vacancy TiO2 and its reaction pathway" (Li Yuhan et al., Science Communications, 2022, Vol. 65, No. 8: 718-728) prepared titanium dioxide (TiO2) containing a large number of surface oxygen vacancies by a one-step calcination method, and applied it to the treatment of formaldehyde, a typical air pollutant. The results show that in the test environment of the flow system, the maximum effective removal rate of formaldehyde can reach 95.05%, which is 1.31 times higher than that of the background sample (72.52%). Studies have shown that TiO2 containing oxygen vacancies can not only enhance the light absorption range, but also use oxygen vacancies to capture photogenerated electrons, effectively inhibiting the recombination of photogenerated electrons and holes, thereby improving the photocatalytic activity. The real-time dynamic monitoring of the catalyst degradation process of formaldehyde by in-situ infrared spectroscopy, combined with density functional theory (DFT) calculations, shows that the oxygen vacancies on the TiO2 surface can effectively enhance the adsorption and activation of formaldehyde molecules, and the large number of delocalized electrons can be injected into the C=O bonds in the formaldehyde molecules and activate and break them, thereby effectively reducing the accumulation of formic acid during the formaldehyde oxidation process and accelerating the efficient oxidation and removal of formaldehyde. However, this method does not take into account the problem that the material will be attenuated when used in a high humidity environment, especially the long-term stability needs to be improved. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a photocatalytic material and a preparation method and application thereof. The photocatalytic material prepared by the present invention has a stable catalytic interface and can maintain good catalytic effect and long-term stability when used for high-humidity VOCs gas treatment.
[0007] The present invention provides a method for preparing a photocatalytic material, comprising the following steps:
[0008] (1) mixing a titanium salt solution and a precipitant under stirring until the pH value is 2-3, then subjecting the mixture to ultrasonic treatment, drying, and vacuum calcining to obtain TiO2 nanoparticles;
[0009] (2) Dispersing TiO2 nanoparticles in anhydrous ethanol to prepare a mixture, treating activated carbon fibers (ACFs) in a silane reagent, and then immersing the ACFs in the mixture for treatment, taking them out, drying them, and calcining them to obtain a photocatalytic material.
[0010] In the present invention, the titanium salt in step (1) is at least one of TiCl4, TiOSO4 and TiSO4, and the concentration of the titanium salt solution is 0.1-1.0 mol / L. Preferably, the titanium salt solution is filtered, and the filtration is carried out by a microfiltration membrane with a pore diameter of 0.10 μm-0.20 μm.
[0011] In the present invention, the precipitant in step (1) is at least one of urea solution, NH4OH solution, etc., and the solution concentration is 0.01-0.05 mol / L.
[0012] In the present invention, the stirring in step (1) can be carried out by various conventional stirring methods to mix the two, preferably magnetic stirring, and the stirring time is 12-36 hours.
[0013] In the present invention, the power of the ultrasonic treatment in step (1) is 200-600 W, preferably 300-400 W, and the treatment time is 10-100 min, preferably 20-60 min.
[0014] In the present invention, the drying temperature in step (1) is 80-200° C. and the drying time is 4-12 hours.
[0015] In the present invention, the vacuum calcination temperature in step (1) is 300-600°C, the vacuum degree is 0.135-0.0135 Pa, and the calcination time is 2-4 hours. Furthermore, the preferred heating rate is 1-4°C / min.
[0016] In the present invention, the mass volume ratio of the TiO2 nanoparticles described in step (2) to anhydrous ethanol is 1 mg: (0.5-1) mL.
[0017] In the present invention, the activated carbon fiber described in step (2) is at least one of polypropylene-based carbon fiber, viscose-based carbon fiber, asphalt-based carbon fiber, etc., preferably asphalt-based carbon fiber.
[0018] In the present invention, the silane described in step (2) is at least one of n-octyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, trifluorooctyltrimethoxy, trichlorooctadecylsilane, etc., preferably heptadecafluorodecyltrimethoxysilane. The concentration of the silane reagent is 0.1-2.0 mol / L, preferably 0.25-1.0 mol / L. The method for preparing the silane reagent can be specifically as follows: dissolving ethylenediamine hydrochloride in a Tris-HCl solution to prepare a 3-5 g / L buffer solution, and then dissolving the silane in the buffer solution to prepare a silane reagent with a concentration of 0.1-2.0 mol / L.
[0019] In the present invention, in step (2), the activated carbon fibers (ACFs) are placed in a silane reagent and treated under stirring conditions for a stirring time of 6-30 hours.
[0020] In the present invention, the immersion in the mixture in step (2) has an immersion time of 2-16 hours, preferably 4-10 hours.
[0021] In the present invention, after taking out in step (2), drying is carried out, the drying temperature is 60-100° C., and the drying time is 3-10 hours.
[0022] In the present invention, the calcination temperature in step (2) is 300-850°C, preferably 500-800°C, and the calcination time is 4-20h, preferably 8-18h. The calcination is carried out in an inert atmosphere, and the carrier gas is any one of N2, Ar, He, etc.
[0023] The photocatalytic material of the present invention is prepared by the above-mentioned method of the present invention. The prepared photocatalytic material is TiO2 nanoparticles containing oxygen vacancies fixed on an activated carbon fiber substrate treated with a silane reagent, and has a stable catalytic interface.
[0024] The present invention also provides an application of the above-mentioned photocatalytic material, which is used for photocatalytic treatment of high-humidity VOCs gas and has good catalytic effect and long-term use stability.
[0025] In the application of the present invention, the high humidity refers to the humidity of the VOCs gas being not less than 50% at normal temperature and pressure, preferably 60%-80%.
[0026] In the application of the present invention, the VOCs refer to organic substances having a boiling point less than or equal to 250°C at normal pressure and a vapor pressure exceeding 0.5 kPa at 25°C, preferably at least one of toluene, acetone, etc.
[0027] In the application of the present invention, the photocatalytic conditions are: the wavelength of the light source is 420-750nm, and the power is 400-600W.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The inventors of the present application have found in their research that the existing photocatalytic materials are not effective when used for treating high-humidity VOCs gases. In particular, although some materials can maintain good effects when used for the first time, the effects will be significantly attenuated after long-term use. Therefore, the inventors of the present application immobilize TiO2 nanoparticles containing oxygen vacancies on ACFs treated with silane reagents to prepare photocatalytic materials for treating high-humidity VOCs gases. This can not only effectively avoid the adverse effects of high humidity on the photocatalytic materials, but also maintain good catalytic effects and good long-term stability.
[0030] (2) TiO2 nanoparticles and activated carbon fibers are bonded via C-Ti bonds. +4 The activated carbon fibers are reduced to Ti +2 It not only expands the response wavelength range of the photocatalytic material, enhances the visible light sensing effect and interfacial charge transfer of the material, and improves the VOCs catalytic effect; in particular, it can improve the stability of the catalyst in long-term use in a high humidity environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the X-ray photoelectron spectrum of the material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The photocatalytic material of the present invention and its preparation method and application effect are further described below in conjunction with specific examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0033] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, were purchased from conventional biochemical reagent stores.
[0034] Example 1
[0035] Dissolve 119 g of TiSO4 in 1 L of deionized water and stir until dissolved. Filter using a 0.20 μm microfiltration membrane to obtain a 0.5 mol / L TiSO4 solution.
[0036] Dissolve 0.08 g of NH4OH in 50 mL of water to prepare a 0.05 mol / L NH4OH solution.
[0037] The TiSO4 solution and the NH4OH solution were mixed under stirring until the pH value was 2.5, magnetically stirred for 24 hours, and then ultrasonically treated at a power of 300 W for 25 minutes, and then dried at a constant temperature of 80°C for 10 hours, placed in an alumina magnetic boat, and then placed in a vacuum tube furnace, and calcined for 2 hours at a vacuum degree of 0.1 Pa and a temperature of 450°C, with a heating rate of 2°C / min, to obtain TiO2 nanoparticles containing oxygen vacancies.
[0038] 0.2 g of ethylenediamine hydrochloride was dissolved in 50 mL of Tris-HCl solution to prepare a buffer solution, and n-octyltrimethoxysilane was dissolved in the buffer solution to prepare a 1.0 mol / L silane reagent. The asphalt-based ACFs were immersed in the silane reagent and stirred at room temperature for 25 h to obtain activated carbon fibers treated with the silane reagent.
[0039] Take 20 mg of the prepared TiO2 nanoparticles and disperse them in 15 mL of anhydrous ethanol to prepare a mixture, and immerse the activated carbon fibers treated with silane reagent in the mixture for 7.5 hours. After taking it out, put it in an oven at 75°C for 8.5 hours, and calcine it in a tube furnace at 650°C and N2 atmosphere for 9 hours to obtain a photocatalytic material. Figure 1 The full-range XPS spectrum of TiO2 / ACFs is shown in Figure 2, and obvious C1s, Ti2p and O1s characteristic peaks are found. Figure 1 The small peak centered at 487.5 eV corresponds to the Ti2p3 / 2 state, indicating that Ti +2 The strong absorption peak at 284.6 eV is speculated to be caused by the delocalization of electrons around the Ti atoms on the carbon fiber surface after the formation of the C-Ti bond, which enhances the electronegativity of the carbon atoms and promotes charge transfer at the interface, thus improving the photocatalytic activity and stability.
[0040] Example 2
[0041] Dissolve 189 g TiCl4 in 1 L deionized water and stir until dissolved. Filter using a 0.2 μm microfiltration membrane to obtain a 1.0 mol / L TiCl4 solution.
[0042] Dissolve 0.12 g of urea in 50 mL of water to prepare a 0.04 mol / L urea solution.
[0043] The TiCl4 solution and the urea solution were mixed under stirring until the pH value was 2.0, magnetically stirred for 30 hours, and then ultrasonically treated at a power of 300 W for 30 minutes, and then dried at a constant temperature of 100°C for 8 hours, placed in an alumina magnetic boat, and then placed in a vacuum tube furnace, and calcined at a vacuum degree of 0.1 Pa and a temperature of 350°C for 4 hours with a heating rate of 2.5°C / min to obtain TiO2 nanoparticles containing oxygen vacancies.
[0044] 0.2 g of ethylenediamine hydrochloride was dissolved in 50 mL of Tris-HCl solution to prepare a buffer solution, and n-octyltrimethoxysilane was dissolved in the buffer solution to prepare a 0.25 mol / L silane reagent. The asphalt-based ACFs were immersed in the silane reagent and stirred at room temperature for 10 h to obtain activated carbon fibers treated with the silane reagent.
[0045] 20 mg of prepared TiO2 nanoparticles were dispersed in 20 mL of anhydrous ethanol to prepare a mixture, and the activated carbon fibers treated with silane reagent were immersed in the mixture for 5 hours. After being taken out, they were placed in an oven at 75°C for 8 hours, and calcined in a tube furnace at 700°C and N2 atmosphere for 8.5 hours to obtain a photocatalytic material.
[0046] Example 3
[0047] Dissolve 32 g of TiOSO4 in 1 L of deionized water and stir until dissolved. Filter using a 0.2 μm microfiltration membrane to obtain a 0.2 mol / L TiOSO4 solution.
[0048] Dissolve 0.09 g of urea in 50 mL of water to prepare a 0.03 mol / L urea solution.
[0049] The TiOSO4 solution and the urea solution were mixed under stirring until the pH value was 3.0, magnetically stirred for 18 hours, and then ultrasonically treated at a power of 350W for 45 minutes, and then dried at a constant temperature of 120°C for 6 hours, placed in an alumina magnetic boat, and then placed in a vacuum tube furnace, and calcined at a vacuum degree of 0.1Pa and a temperature of 600°C for 2 hours with a heating rate of 2.5°C / min to obtain TiO2 nanoparticles containing oxygen vacancies.
[0050] 0.2 ethylenediamine hydrochloride was dissolved in 50 mL Tris-HCl solution to prepare a buffer solution, and n-octyltrimethoxysilane was dissolved in the buffer solution to prepare a 3.0 mol / L silane reagent. The asphalt-based ACFs were immersed in the silane reagent and stirred at room temperature for 20 h to obtain activated carbon fibers treated with the silane reagent.
[0051] Take 20 mg of the prepared TiO2 nanoparticles and disperse them in 10 mL of anhydrous ethanol to prepare a mixture, immerse the activated carbon fibers treated with silane reagent in the mixture, and immerse them for 6 hours. After taking them out, put them in an oven at 85°C for 7 hours, and calcine them in a tube furnace at 350°C and N2 atmosphere for 14 hours to obtain a photocatalytic material.
[0052] Example 4
[0053] The same as Example 1, except that silane is replaced by heptadecafluorodecyltrimethoxysilane to obtain the final photocatalytic material.
[0054] Example 5
[0055] The same as Example 1, except that silane is replaced by trifluorooctyltrimethoxy to obtain the final photocatalytic material.
[0056] Example 6
[0057] The same as Example 1, except that silane is replaced by trichlorooctadecylsilane to obtain the final photocatalytic material.
[0058] Example 7
[0059] The same as Example 1, except that the asphalt-based carbon fiber is replaced by polypropylene-based carbon fiber to obtain the final photocatalytic material.
[0060] Example 8
[0061] The same as Example 1, except that the asphalt-based carbon fiber is replaced by viscose-based carbon fiber to obtain the final photocatalytic material.
[0062] Comparative Example 1
[0063] The same as Example 1, except that the TiO2 nanoparticles are not treated with oxygen vacancies, that is, the final photocatalytic material is obtained by using TiO2 nanoparticles without oxygen vacancies.
[0064] Comparative Example 2
[0065] The method is the same as Example 1, except that step (2) is not performed, and the TiO2 nanoparticles containing oxygen vacancies obtained in step (1) are directly used as the photocatalytic material.
[0066] Comparative Example 3
[0067] The same as Example 1, except that: in step (1), ultrasonic treatment is not performed to obtain the final photocatalytic material.
[0068] Comparative Example 4
[0069] The method is the same as Example 1, except that step (1) does not use vacuum calcination, but only uses high temperature calcination to obtain the final photocatalytic material.
[0070] Comparative Example 5
[0071] The same as Example 1, except that the activated carbon fibers are not treated with a silane reagent to obtain the final photocatalytic material.
[0072] Comparative Example 6
[0073] The same as Example 1, except that the concentration of the silane reagent was adjusted to 4.0 mol / L to obtain the final photocatalytic material. The results showed that due to the excessively high concentration, shrinkage and agglomeration occurred during the sintering process, which had an adverse effect on the specific surface area and pore volume of the catalyst, and reduced the photocatalytic performance of the material.
[0074] Comparative Example 7
[0075] The same as Example 1, except that anhydrous ethanol is replaced by 75% ethanol solution to obtain the final photocatalytic material.
[0076] Comparative Example 8
[0077] The same as Example 1, except that the silane reagent is first added to the mixture prepared by dispersing TiO2 nanoparticles in anhydrous ethanol, and then the activated carbon fiber is immersed in the mixture to obtain the final photocatalytic material.
[0078] Test Example 1
[0079] The photocatalytic materials prepared in the examples of the present invention and the comparative examples were used to treat high-humidity VOCs gas: the VOCs in the gas was toluene with a concentration of 1000 mg / m 3 , relative humidity is 70%.
[0080] 0.4 g of catalyst was placed in a double-layer quartz cold trap photocatalytic purification device with a volume of 50 mL. After high-humidity VOCs gas was introduced, the sample was irradiated with a xenon lamp (CEL-HXF300) with a wavelength of 420 nm and a power of 500 W for 1.5 h, and the CO2 in the system was detected with a gas chromatograph (GC-9790plus, Fuli). The CO2 generation rate is shown in Table 1.
[0081] Table 1 Experimental results of different embodiments and comparative examples
[0082]
[0083]
[0084] Test Example 2
[0085] The photocatalytic materials prepared in the embodiments of the present invention and the comparative examples were used to treat high-humidity VOCs gas: the VOCs in the gas was acetone with a concentration of 1000 mg / m 3 , relative humidity is 60%.
[0086] 0.4 g of catalyst was placed in a double-layer quartz cold trap photocatalytic purification device with a volume of 50 mL. After high-humidity VOCs gas was introduced, the sample was irradiated with a xenon lamp (CEL-HXF300) with a wavelength of 600 nm and a power of 500 W for 1.5 h, and the CO2 in the system was detected with a gas chromatograph (GC-9790plus, Fuli). The CO2 generation rate is shown in Table 2.
[0087] Table 2 Experimental results of different embodiments and comparative examples
[0088]
[0089]
[0090] It can be seen from Table 1 and Table 2 that the photocatalytic material prepared by the present invention has a stable catalytic interface and can maintain good catalytic effect and long-term stability when used for high-humidity VOCs gas treatment. However, if any of the technical features of the present invention is missing, the effect is not very ideal.
Claims
1. A method for preparing a photocatalytic material, characterized in that The following steps are involved: (1) mixing a titanium salt solution and a precipitant under stirring until the pH value is 2-3, then subjecting the mixture to ultrasonic treatment, drying, and vacuum calcining to obtain TiO2 nanoparticles; (2) Dispersing TiO2 nanoparticles in anhydrous ethanol to prepare a mixture, treating the activated carbon fibers in a silane reagent, and then immersing the activated carbon fibers in the mixture for treatment. After taking out, the carbon fibers are dried and calcined to obtain a photocatalytic material.
2. The method according to claim 1, characterized in that: The titanium salt in step (1) is at least one of TiCl4, TiOSO4 and TiSO4, and the concentration of the titanium salt solution is 0.1-1.0 mol / L.
3. The method according to claim 2, characterized in that: The titanium salt solution in step (1) is filtered using a microfiltration membrane with a pore diameter of 0.10 μm to 0.20 μm.
4. The method according to claim 1, characterized in that: The precipitant in step (1) is at least one of a urea solution and an NH4OH solution, and the solution concentration is 0.01-0.05 mol / L.
5. The method according to claim 1, characterized in that: The stirring in step (1) is carried out by magnetic stirring, and the stirring time is 12-36 hours.
6. The method according to claim 1, characterized in that: The power of the ultrasonic treatment in step (1) is 200-600 W, preferably 300-400 W, and the treatment time is 10-100 min, preferably 20-60 min.
7. The method according to claim 1, characterized in that: The drying temperature in step (1) is 80-200°C and the drying time is 4-12h.
8. The method according to claim 1, characterized in that: The vacuum calcination temperature in step (1) is 300-600°C, the vacuum degree is 0.135-0.0135 Pa, and the calcination time is 2-4h; preferably, the heating rate is 1-4°C / min.
9. The method according to claim 1, characterized in that: The mass volume ratio of the TiO2 nanoparticles to anhydrous ethanol in step (2) is 1 mg: (0.5-1) mL.
10. The method according to claim 1, characterized in that: The activated carbon fiber described in step (2) is at least one of polypropylene-based carbon fiber, viscose-based carbon fiber, and asphalt-based carbon fiber, preferably asphalt-based carbon fiber.
11. The method according to claim 1, characterized in that: The silane described in step (2) is at least one of n-octyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, trifluorooctyltrimethoxy, and trichlorooctadecylsilane, preferably heptadecafluorodecyltrimethoxysilane.
12. The method according to claim 1 or 11, characterized in that: The concentration of the silane reagent is 0.1-2.0 mol / L, preferably 0.25-1.0 mol / L.
13. The method according to claim 1, 11 or 12, characterized in that: The specific method for preparing the silane reagent is: dissolving ethylenediamine hydrochloride in a Tris-HCl solution to prepare a 3-5 g / L buffer solution, and then dissolving silane in the buffer solution to prepare a silane reagent with a concentration of 0.1-2.0 mol / L.
14. The method according to claim 1, characterized in that: Step (2) treating the activated carbon fiber in a silane reagent under stirring conditions for 6-30 hours.
15. The method according to claim 1, characterized in that: The immersion in the mixture in step (2) has an immersion time of 2-16 hours, preferably 4-10 hours.
16. The method according to claim 1, characterized in that: After taking out in step (2), the product is dried at a temperature of 60-100°C for a time of 3-10 hours.
17. The method according to claim 1, characterized in that: The calcination temperature in step (2) is 300-850°C, preferably 500-800°C; the calcination time is 4-20h, preferably 8-18h.
18. The method according to claim 1 or 17, characterized in that: The calcination in step (2) is carried out in an inert atmosphere, and the carrier gas is any one of N2, Ar, and He.
19. A photocatalytic material, characterized in that It is prepared by the method according to any one of claims 1 to 18.
20. The photocatalytic material prepared by the method according to any one of claims 1 to 18 or the use of the photocatalytic material according to claim 19, characterized in that: Used for photocatalytic treatment of high-humidity VOCs gases, it has good catalytic effect and long-term stability.
21. The use according to claim 20, characterized in that: The high humidity refers to that the humidity of the VOCs gas is not less than 50% at normal temperature and pressure, preferably 60%-80%.
22. The use according to claim 20, characterized in that: The VOCs refer to organic substances with a boiling point less than or equal to 250°C at normal pressure and a vapor pressure greater than 0.5 kPa at 25°C, preferably at least one of toluene and acetone.
23. The use according to claim 20, characterized in that: The photocatalytic conditions are as follows: the wavelength of the light source is 420-750nm and the power is 400-600W.
Citation Information
Patent Citations
Method for preparing titanic oxide nano powder with visual light catalytic activity
CN101289223A
Preparation method of activated carbon fiber loaded titanium dioxide photocatalyst
CN103100378A
Method for supporting nanometer titanium dioxide on active carbon fibers
CN105268400A
Photocatalysis active carbon fiber and preparation method thereof
CN106179295A
Preparation method, testing device and testing method of TiO2 / ACF composite material
CN114904503A